Positivisme dan Implikasinya terhadap Ilmu dan Penegakan Hukum oleh Mahkamah Konstitusi (Analisa Putusan Nomor 46/PUU-XIV/2016) - Tundjung Herning Sitabuana; Ade Adhari (The Constitutional Court of the Republic of Indonesia, 2020)
This paper reveals fundamental questions about the implications of the school of positivism for science and law enforcement in the Constitutional Court. The study results show First, at the level of jurisprudence, this school understands its adherents that jurisprudence as “a normological understanding of the meaning of positive law (normological apprehension of the meaning of positive law)”. The development of jurisprudence is then carried out through the activities of studying, researching and teaching various positive laws, “which in the end the development of jurisprudence is more towards” dogmatic jurisprudence “. Second, at the level of law enforcement in the Constitutional Court, the implication of judges is to base the process of law enforcement as stipulated in the positive norms of statutory regulations. Upholding the law becomes synonymous with enforcing positive rules. Judges as legal bearers are practically proficient in reading and sounding positive law in their legal decisions. Decision of the Constitutional Court Number 46/PUUXIV/2016 related to the existence of adultery in the Criminal Code is one of the decisions that have a strong influence from this school.